Política de transferência de renda e desenvolvimento local: o programa Bolsa família no município de Pedra Grande/RN - Silva, Ana Paula Queiroz da (2008)
The Family Scolarship Program while public politics of intersectorial form developed by Social Development Department and Famine Combat having with partner the Education Department and Health Department inaugurate in the country a new integrity way of the public politics, reinforcing a precept of 2004 Social Protection National Politics (PNAS 2004) that places the social protection while allied to the social and human development. The research INCOME TRANSFER AND LOCAL DEVELOPMENT: the family scolarship program in Pedra Grande-RN municipally had as aim to avaluate the permanent Family Scolarship Program as a possible element in local development of Pedra Grande-RN municipally understood as capacity expansion and improvement of life quality from its users. For this means we elaborate specifically the families` socio-economical profile; we avaluate the program repercussion in these families` lives; we analyse in which proportion occurred the capacity expansion and improvement of life quality of the users. The methodologic process was constituted by: literarture review about Income Transfer, Social Vulnerability, Development and Public Politics Avaluation to the criation of a theoric picture analysis. The documental research joined to the Social Development Department and Famine Combat of Pedra Grande Municipally Hall to obtain of the aims, program goals, and the profile of users. And finally, carrying out the interviews with the managers and experts of the Municipally Program and focal groups with the users to avaluate the permanent of the Program starting by the points of view of those ones. It was verified that the program expand the capacity (food, consumer goods and services, bank services access and wages) and improvement in life quality of the users. Nevertheless, there are deficiencies in coming with conditionality and from the use of resources the by families users